Factorise

Asked by Shivam Saxena | 13th Sep, 2010, 10:54: PM

Expert Answer:

6 - 2√2x - x2/2 - x2 =
6 - 2√2x - x2 - x2/2 =
(3√2√2) - 2√2x - x2 - x2/2 =                       ... note that 3√2√2 = 3 x 2 = 6
(3√2√2) - 3√2x + √2x - x2 - x2/2 =
(3√2(√2 - x) + x(√2 - x) - x2/2 =
(√2 - x)(3√2 + x) - x2/2 =
[x/√2 - (√2 - x)1/2(3√2 + x)1/2][x/√2 + (√2 - x)1/2(3√2 + x)1/2]        ... (a - b)(a + b) = a2 - b2
regards,
Team,
TopperLearning.

Answered by  | 14th Sep, 2010, 06:50: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.